Creación de un Plan de Animación Turística para el Hotel Sebastián, ubicado en el Barrio la Mariscal del Distrito Metropolitano de Quito - García Moromenacho, Lorena Patricia (2010)
The present work of education is a project that seeks to create a plan of tourist animation in the Sebastian Hotel located in “The Mariscal Area” of Quito Metropolitan District. This research is based on precedents like the need of in novating the tourist sector, that´s why this project takes into account: Methodology: it is based on the instruments and research types, as well as the sources of information (primary and secondary). The characterization of study area: defining the origin, corporate image, mission, vision, hotel services, capacity of service, administrative area, organization chart and description of job positions of the internal part of the Hotel Sebastian. The situational Diagnosis of the Hoptel Has nowadays and that recognizes as animation, the staff contact with the customer. With previous data, the problema was determined for which a plan of animation was proposed as a solution. The hotel animation describes objectives justufication and structure of the passive activity. To conclude the Project and summarize the leaming, conclusions and recommendations are carried out about the development that was acquired in the course of the course of the same one.